The Relationship Between Values and Interests - Samia Maqbool Niazi (UIN Sunan Gunung Djati Bandung, 2014)
Some writers equate values with interests. Philipp Heck defines interests, which he treats as synonymous with values, as “all things that man holds dear, and all ideals which guide man’s life. ”There are many writers who distinguish between the two concepts and go into the details of the distinction, as is explained below. There is an apparent relationship between interests, principles, rules, values, objectives and other similar terms. Our main purpose is to find the link between interests and values, because the term interest dominates all legal discourse. In simple terms, interests recognized and enforced by law become rights. To elaborate the meaning of interests in relation to values, we need to refer to the work of Roscoe Pound, however briefly.